2014
DOI: 10.1002/ejlt.201400016
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating eggs from different poultry species by fatty acids and volatiles profiling: Comparison of SPME‐GC/MS, electronic nose, and principal component analysis method

Abstract: Fatty acid profiles and volatile composition in the yolks of conventional eggs from seven different species (duck, free‐range chicken, silky chicken, quail, pigeon, goose, and chicken) were compared using GC–MS and electronic nose (E‐nose). The results showed that there were significant differences among the fatty acid profiles of the seven avian eggs. Goose eggs contained the highest contents of saturated and monounsaturated fatty acids but the lowest content of polyunsaturated fatty acids (PUFA), and the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 35 publications
(47 reference statements)
2
49
0
Order By: Relevance
“…E‐nose has many advantages over traditional analytical tools and offers a potentially new, non‐invasive, cost‐effective approach to detect and discriminate volatile organic compounds (VOCs) from different food samples . The principle of E‐nose to distinguish between the differences or variations in samples or treatments is based on the overall response of sensor arrays . But it could not identify odor compounds as precisely as gas chromatography‐mass spectrometry (GC‐MS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E‐nose has many advantages over traditional analytical tools and offers a potentially new, non‐invasive, cost‐effective approach to detect and discriminate volatile organic compounds (VOCs) from different food samples . The principle of E‐nose to distinguish between the differences or variations in samples or treatments is based on the overall response of sensor arrays . But it could not identify odor compounds as precisely as gas chromatography‐mass spectrometry (GC‐MS).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The principle of E-nose to distinguish between the differences or variations in samples or treatments is based on the overall response of sensor arrays. 7 But it could not identify odor compounds as precisely as gas chromatography-mass spectrometry (GC-MS). Solid-phase microextraction (SPME), which combines sampling, analyte isolation, enrichment, and clean-up into one step, is a versatile, effective, and easily automated assay for VOC sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in rheological properties of egg yolk are caused by chemical composition of yolks from hens, geese, and quail (differences in water and lipid content). In the publication [25] it is shown that goose eggs (especially yolk) contained the highest contents of saturated and monounsaturated fatty Fluid dynamics of liquid egg productsacids but the lowest content of polyunsaturated fatty acids (PUFA). The ω-3 PUFA content and the ω-6/ω-3 ratio were higher in the yolks of goose.…”
Section: Discussionmentioning
confidence: 99%
“…The sum fatty acid percentages (g/100g of oil) in the egg yolks of the four properties decreased in the order of monounsaturated (MUFA) ( 6,28,29,30 .…”
Section: Fatty Acids Contentmentioning
confidence: 98%